Substantial genetic divergence and lack of recent gene flow support cryptic speciation in a colour polymorphic bumble bee (Bombus bifarius) species complex. (15th January 2020) - Ghisbain, Guillaume; Lozier, Jeffrey D.; Rahman, Sarthok Rasique; Ezray, Briana D.; Tian, Li; Ulmer, Jonah M.; Heraghty, Sam D.; Strange, James P.; Rasmont, Pierre; Hines, Heather M.
Abstract: Phenotypic polymorphism can constitute an inherent challenge for species delimitation. This issue is exemplified in bumble bees ( Bombus ), where species can exhibit high colour variation across their range, but otherwise exhibit little morphological variation to distinguish them from close relatives. We examine the species status of one of the most abundant North American bumble bees, Bombus bifarius Cresson, which historically comprised two major taxa, bifarius s.s. and nearcticus . These lineages are recognized primarily by red and black variation in their mid‐abdominal coloration; however, a continuum from black ( nearcticus ) to red ( bifarius s.s.) variation has led to their historic synonymization. Integrating mitochondrial and nuclear data and whole‐genome sequencing, we reveal a high level of both mitochondrial and nuclear divergence delimiting two morphologically cryptic species – the red bifarius s.s. and the colour‐variable (black to red) nearcticus . Population genomic analysis supports an absence of recent genomic admixture and a strong population structure between the two clades, even in sympatry. Species distribution models predict partially differentiated niches between the genetically inferred clades with annual precipitation being a leading differentiating variable. The bifarius s.s. lineage also occupies significantly higher elevations, with regions of sympatry being among the highest elevations in nearcticus . Our data also support a subspecies‐level divergence between the broadly distributed nearcticus and the island population vancouverensis . In this paper, we formally recognize the two species, Bombus bifarius Cresson and Bombus vancouverensis Cresson, the latter including the subspecies B. vancouverensis vancouverensis comb.n. and B. vancouverensis nearcticus comb.n ., with vancouverensis the name bearer due to year priority. Abstract : Mitochondrial and nuclear genomic data are used to assess and redefine the species status of the common widespread western North American bumble bee species Bombus bifarius Cresson. Bombus bifarius s.l. is determined to comprise two species that fail to admix in a hybrid zone: western widespread Bombus vancouverensis, and Bombus bifarius, confined to the Colorado plateau. These species are considered morphologically cryptic aside from somewhat overlapping differences in colour, with historic species confusion created by colour polymorphism related to mimicry.